Synthetic musk in seafood products from south Europe using a quick, easy, cheap, effective, rugged and safe extraction method. (1st June 2016) - Saraiva, M.; Cavalheiro, J.; Lanceleur, L.; Monperrus, M.
Highlights: QuEChERS method was optimized to extract musk compounds from lipid containing matrices. Musk levels were determined in seafood products from the European southwest coast. Concentrations of musks were also determined in different salmon organs. Abstract: This study aims at developing a method for the determination of 9 synthetic musk compounds in seafood products by combining the quick, easy, cheap, effective, rugged, and safe (QuEChERS) method and determination by gas chromatography mass spectrometry (GC–EI–MS). Method detection limits (MDL) ranging between 0.001 and 1.94 ng g −1 were obtained. The linearity is higher than 0.9899 in the range MDL – 100 ng g −1 with precision below 18% and recoveries between 46% and 120% were obtained. The method was applied to quantify musk compounds in seafood products from the European southwest coast (oysters, mussels, salmon organs, glass eels). Galaxolide and Tonalide exhibited the highest concentration levels ranging between MDL – 96.4 ng g −1 and MDL – 6.85 ng g −1, respectively. Contamination levels observed for the two nitro musks (musk xylene and musk ketone) are significantly lower ranging between MDL – 0.6 ng g −1 and MDL – 0.09 ng g −1, respectively. Analysis of different organs of salmons showed higher concentrations in liver and gonad than in muscle tissues.